Morphological pattern of glomerular diseases in adult nephrotic syndrome. - Huq, N; Khatun, H; Jinnah, SA (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):652-7 The abstract of this article is available on the PubMed website